Removal of Cr(VI) from Aqueous Solution by Polypyrrole/Hollow Mesoporous Silica Particles - Linlin Du (Nanomaterials, 2020)
Abstract: The removal of Cr(VI) in wastewater plays an important role in human health and environment. In this work, polypyrrole/hollow mesoporous silica particle (PPy/HMSNs) adsorbents have been newly synthesized by in-situ polymerization, which prevent the aggregation of pyrrole in the process of polymerization and exhibit highly selective and powerful adsorption ability for Cr(VI). The adsorption process was in good agreement with the quasi-second-order kinetic model and the Langmuir isotherm model. And the maximum adsorption capacity of Cr(VI) was 322 mg/g at 25 °C. Moreover, the removal rate of Cr(VI) by PPy/HMSNs was ~100% in a number of binary systems, such as Cl−/Cr(VI), NO3−/Cr(VI), SO42−/Cr(VI), Zn2+/Cr(VI), Fe3+/Cr(VI), Sn4+/Cr(VI), and Cu2+/Cr(VI). Thus, the PPy/HMSNs adsorbents have great potential for the removal of Cr(VI) in wastewater.